EXPRESSION OF PRAGMATIC GOAL IN POSITIVE DESIRE UNITS (Global Conference on Multidisciplinary Research and Innovation, 2026)
In this article, the units of positive desire in the Uzbek language were analyzed pragmatically, and a number of pragmatic purposes expressed in them, such as informing, asking, ordering, begging, persuading, warning, advising, apologizing, and offering, were explained. It is analyzed that one unit of positive desire expresses different pragmatic goals in different speech situations.
Keywords: units of positive desire, pragmatic goal, intention, speech situation, initial intention, resulting intention, communicative goal, communication.